2020
DOI: 10.1101/2020.02.28.20029199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the COVID-19 Outbreak on the Medical Treatment of Chinese Children with Chronic Kidney Disease (CKD) : A Multicenter Cross-section Study in the Context of a Public Health Emergency of International Concern

Abstract: Objective: To investigate the impact of the COVID-19 outbreak on the medical advice seeking of Chinese children with chronic kidney disease (CKD). Materials and Methods: An anonymous online questionnaire survey was conducted in 17 pediatric nephropathy diagnosis and treatment centers in China. The questions collected basic information on the patients and their parents and data on changes in the approach to medical treatment and their needs in the context of the outbreak etc.This is a Multicenter Cross-section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Children with underlying diseases, such as malignancies, cirrhosis, chronic kidney disease, cardiovascular or pulmonary diseases or immunosuppression may experience more severe symptoms, like respiratory distress syndrome, septic shock, deep acidosis, and respiratory or even cardiovascular collapse (3,15).…”
Section: Clinical Manifestations Of Covid-19 In Pediatricsmentioning
confidence: 99%
“…Children with underlying diseases, such as malignancies, cirrhosis, chronic kidney disease, cardiovascular or pulmonary diseases or immunosuppression may experience more severe symptoms, like respiratory distress syndrome, septic shock, deep acidosis, and respiratory or even cardiovascular collapse (3,15).…”
Section: Clinical Manifestations Of Covid-19 In Pediatricsmentioning
confidence: 99%
“…In another study, Haslak et al (15) have investigated the concerns regarding the management of childhood-onset autoinflammatory diseases during the era of COVID-19. Their findings showed that children with childhood-onset autoinflammatory disorder who received biologic treatment and/or colchicine may not be at higher risk of infection from COVID-19 or experiencing severe disease course (16). The results of these two studies highlight the importance of reliance on the therapeutic regimen during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…In this regards, Zhang et al (16) have also investigated the impact of COVID-19 pandemic on the treatment of children with chronic kidney disease (CKD) in China. In line with our findings, Zhang et al (16) showed that the majority of the parents (81.1%) were concerned about the condition of their children. Moreover, they found that only 1.12 of the parents decided to stop the medicines or treatment of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In addition, because of contact with health care professionals at our center children with cancer may have been informed better regarding COVID-19 risks and prevention, and had access to psychosocial support if necessary. 17 Also, the disruption of care during COVID-19 may be worrisome, 18,19 but outpatient care was continued completely at our center.…”
Section: Discussionmentioning
confidence: 99%